The Influences of Firm’s Resource and Network Resource towards Taiwanese Start-ups’ Entry Modes to China: an analysis of the Resource-based view. - Lo, Tzutung (2014)
This study attempts to understand the internationalisation of Start-ups from emerging county (EE) to another emerging county by examining seven Taiwanese start-ups who expanded into China market. Under the framework of Resource-based views (RBV), this study explores to what extent the firm’s resources and network resource can explain entry mode choices by the company. Also, this study chose technological firms and knowledge-intensive firms as a research case in order to realise the difference of high and low technological resources affecting the entrepreneur’s entry strategy. These Taiwanese’s start-ups have better opportunity-seeking behaviour than establish firm. The advantage of recognising opportunities and good network relationship with local partners enable these start-ups exploit their firm’ resource to china market. But, in terms of the influence of entry mode, this research findings highlight that the institutional effects show greater power than a firm’s resources and capabilities. Moreover, it also demonstrates that even those Taiwanese start-ups have competitive advantages based on their held resources but they are still similar to well-established firms who heavily rely on network relationship to exploit opportunities of internationalisation.